Fusional Vergence Detected by Prism Bar and Synoptophore in Chinese Childhood Intermittent Exotropia - Tao Fu; Jing Wang; Moran Levin; Qing Su; Dongguo Li; Junfa Li (Journal of Ophthalmology)
Purpose. To measure the changes in fusional vergence in Chinese children with intermittent exotropia (IXT) and the association with the control of IXT. Methods. Ninety-two patients with IXT (8–15 years old) were compared with 86 controls. Exodeviation control was evaluated using the Revised Newcastle Control Score. Angle of deviation was measured using prism and alternate cover testing at distance and near. Fusional vergence was measured using prism bar and synoptophore. This study was registered with ChiCTR-RCC-13003920. Results. Using prism bar, convergence break points were lower whereas divergence break points were higher in children with IXT at distance (P<0.001) and near (P<0.001) compared with controls. There was no significant difference in mean divergence amplitudes between the two groups when testing using a synoptophore (P=0.53). In children with IXT, the distance between recovery point and break point in both convergence (distance: P=0.02; near: P=0.02) and divergence (distance: P<0.001; near: P<0.001) was larger than controls when detected by prism bar and synoptophore (convergence: P=0.005; divergence: P=0.006). Conclusions. Children with IXT have reduced convergence amplitudes as detected by both prism bar and synoptophore.